The Arthurian way of death : the English tradition - Cherewatuk, Karen; Whetter, K. S. (Kevin Sean), 1969- (Arthurian studies, 2009)
It is arguably the tragic end to Arthur's kingdom which gives the myth its exceptional resonance and power. The essays in this volume explore the presentation of death and dying in Arthurian literature and film produced in England and America from the mid.